Gotong Royong as the Core Principle of Pancasila and Its Relevance as Peace Education in Social Studies Learning - Sariyatun Sariyatun (Universitas Sebelas Maret, 2021)
This paper seeks to investigate the position of gotong royong (mutual cooperation) in Pancasila and its relevance as peace education in social studies learning. This paper is an effort as well as an offer to build an inclusive culture in order to solve the problems of bullying and intolerance in education. This paper used qualitative method with literature study approach by analyzing literatures related to the research corpus, i.e. Pancasila, mutual cooperation, peace education, and social studies learning. The results showed that mutual cooperation as the core principle of Pancasila is a treasure of Indonesian culture which is closely related to the substance of divine values, deliberation and consensus, kinship, justice and tolerance (humanitarianism). These values have strategic values to be conveyed in the social studies learning process in the classroom in order to foster a culture of peace for students.